Sharing Science Made Simple: Exploring the Quality and Readability of Published Lay Summaries - Sudharshan, Anjana; Khameraj, Breanna; Budincevic, David; Halabian, Negar (The Meducator, 2024)
Lay summaries exist to bridge the gap that separates the scientific community from the general public. To foster improved science communication, this study examined the overall quality and readability of published lay summaries across peer-reviewed journals. We obtained 200 lay summaries published in four science journals: eLife, PLOS Medicine, Proceedings of the National Academy of Science (PNAS), and the Journal of Hepatology. Over 900 students across three semesters participated as raters of each summary using a rubric developed to assess the overall quality, accuracy, and accessibility of lay summaries across these journals. The Flesch Reading Ease formula was used to determine the readability of the highest and lowest scoring summaries from each journal. eLife and the Journal of Hepatology had the highest and lowest mean scores for overall quality of 15.6 and 11.7 out of 20, respectively. There were statistically significant differences in accuracy and accessibility found across all journals (p<0.0001). eLife had the highest scoring lay summary for readability. The differences in and lack of consistent scoring across journals with the rubric indicate that deficits exist in the overall quality and readability of published lay summaries. These findings may support the development of guidelines that incorporate elements of the rubric used to write effective lay summaries.